2017
DOI: 10.1186/s12885-017-3453-8
|View full text |Cite
|
Sign up to set email alerts
|

CpG promoter methylation of the ALKBH3 alkylation repair gene in breast cancer

Abstract: BackgroundDNA repair of alkylation damage is defective in various cancers. This occurs through somatically acquired inactivation of the MGMT gene in various cancer types, including breast cancers. In addition to MGMT, the two E. coli AlkB homologs ALKBH2 and ALKBH3 have also been linked to direct reversal of alkylation damage. However, it is currently unknown whether ALKBH2 or ALKBH3 are found inactivated in cancer.MethodsMethylome datasets (GSE52865, GSE20713, GSE69914), available through Omnibus, were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…This specific SNP was located within an intron in Alkylated DNA Repair Protein AlkB Homolog 3 (ALKBH3). This gene has been specifically associated with cell survival in various forms of cancer in humans (Tasaki et al, 2011;Stefansson et al, 2017). This SNP was also located in a region described by Peters et al (2012) that contained several SNP windows associated with various forms of ADG calculated from birth to weaning, weaning to yearling, and birth to yearling in Brangus heifers.…”
Section: Resultsmentioning
confidence: 93%
“…This specific SNP was located within an intron in Alkylated DNA Repair Protein AlkB Homolog 3 (ALKBH3). This gene has been specifically associated with cell survival in various forms of cancer in humans (Tasaki et al, 2011;Stefansson et al, 2017). This SNP was also located in a region described by Peters et al (2012) that contained several SNP windows associated with various forms of ADG calculated from birth to weaning, weaning to yearling, and birth to yearling in Brangus heifers.…”
Section: Resultsmentioning
confidence: 93%
“…ALKBH4 belongs to the AlkB family of non-heme Fe (II)/a-ketoglutarate-dependent dioxygenases, whose function have been implicated in the repair of methylation damage in DNA and RNA (Lee et al, 2005). Available evidences also indicate that several members of AlkB family, such as ALKBH3 and ALKBH5, are closely linked to the inhibition of tumorigenesis and progression in various human cancers (Stefansson et al, 2017;Wang et al, 2018;Zhu et al, 2019). ALKBH4 has been previously illustrated in mediating demethylation of a monomethylated site in actin and depletion of ALKBH4 contributes to defects in cytokinesis and cell motility (Li et al, 2013), however, the underlying molecular mechanisms of ALKBH4 in tumor remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, considering that ALKBH2 or ALKBH3 is found to be overexpressed in many types of cancer, including prostate adenocarcinoma, non-small cell lung carcinoma, and head and neck cancer, chemotherapy developed from ALKBH-dependent alkylation repair may be promising (Konishi et al, 2005;Gilljam et al, 2009;Tasaki et al, 2011;Pilžys et al, 2019). Additionally, Stefansson et al (2017) suggested that promoter methylation status of the ALKBH3 gene in several breast cancers correlates with poor prognosis. In addition, a positive correlation exists between the promoter methylation and cellular N 3 meC levels in several breast cancer cell lines, suggesting a potential direction for alkylation chemotherapy (Stefansson et al, 2017).…”
Section: Alkbh-dependent Alkylation Repair and Cancer Chemotherapymentioning
confidence: 99%